Nanoparticles Loaded with Wnt and YAP/Mevalonate Inhibitors in Combination with Paclitaxel Stop the Growth of TNBC Patient‐Derived Xenografts and Diminish Tumorigenesis. Issue 11 (12th August 2020) - Sulaiman, Andrew; McGarry, Sarah; El‐Sahli, Sara; Li, Li; Chambers, Jason; Phan, Alexandra; Al‐Kadi, Emil; Kahiel, Zaina; Farah, Eliya; Ji, Guang; Lee, Seung‐Hwan; Inampudi, Krishna K.; et al.
Abstract: Triple negative breast cancer (TNBC) accounts for the majority of breast cancer‐related deaths and remains the hardest breast cancer to treat due to the lack of specific therapeutic targets. While chemotherapy is the mainstay of systemic treatment for TNBC, it is associated with chemotherapy‐induced cancer stem cells (CSCs) and tumor regeneration. Here, it is found that Wnt and YAP target genes that have been closely associated with CSCs are highly expressed in TNBC patient tumors and negatively correlated with patient survival. Therefore, a nanotherapeutic strategy is employed, using nanomaterials that are approved by the FDA, and two co‐delivery nanoparticle platforms (NPs) are developed to target TNBC. These NPs contain Wnt inhibitor PRI‐724 (in clinical trials) and YAP/mevalonate inhibitor simvastatin (FDA‐approved). Toward clinical translation, nanotherapeutic efficacy is assessed in clinically relevant patient‐derived xenograft (PDX) models. These NPs in combination with the chemotherapeutic drug paclitaxel effectively halt the growth of both paclitaxel‐resistant and paclitaxel‐sensitive PDX tumors, and diminish the paclitaxel‐induced CSC enrichment around two to fourfold. Importantly, NPs also decrease the paclitaxel‐enhanced PDX tumorigenesis after secondary transplantation. Together, this study demonstrates the efficacy of two NP platforms using clinically translatable TNBC PDX models, suggesting their application potential for the treatment of TNBC. Abstract : A new nanotherapy for the effective treatment of triple negative breast cancer is described and validated in clinically relevant patient‐derived xenograft (PDX) models. The nanoparticles containing Wnt and Yap inhibitors in combination with the chemotherapeutic drug paclitaxel effectively halt the growth of both paclitaxel‐resistant and paclitaxel‐sensitive PDX tumors, and diminish tumorigenesis, suggesting potential for application in the clinic.